Modeling Runoff and Sediment Yield in Highly Gullied Regions of Kashmir using SWAT Model: A Case Study of Lolab Watershed - Dar Sarvat Gull; Ayaz Mehmood Dar (Journal of the Civil Engineering Forum, 2020)
Soil erosion in highly gullied regions of Kashmir valley is a serious global issue due to its impacts on economic productivity and environmental consequences such as land disintegration and one of the most affected areas is Lolab which is flood-prone and has witnessed several disastrous floods in the past. This means assessment of hydrological behavior should be highly prioritized and the most problematic sub-basins contributing to the erosion and excessive runoff identified to formulate and apply proper management strategies. This study integrated the Soil and Water Assessment Tool (SWAT) with Arc software to simulate the runoff and sediment yield of Lolab Watershed. The method was applied due to its flexibility in inputting data requirements and the capability to model larger catchments and mountainous areas. Meanwhile, sensitivity analysis showed the most sensitive four parameters for runoff estimation with the initial soil conservation service curve number II rated to be the highest and two others were found for sediment estimation with channel erodibility factor rated highest. The calibration of the values of these sensitive parameters led to the provision of reliable NashSutcliffe (NSE) and Coefficient of determination(R2) efficiencies which makes SWAT a good analyzing tool to assess the hydrological behavior of highly gullied region and un-gauged basins of Kashmir. These factors were found to be above 0.90 for both runoff and sediment yield and the sediment yield rates were estimated using SWAT at individual sub-basin levels after which a prioritization map was prepared to determine the most problematic sub-basins in the watershed.